The Role of Mindfulness in Reducing Organizational Change Stress: A Qualitative Analysis of a Fintech Company - Dipoatmodjo, Tenri Sayu Puspitaningsih (Malaqbi Publisher, 2025)
This qualitative study explores the role of mindfulness in mitigating organizational change stress within a fintech company. Through in-depth interviews with 25 employees undergoing significant transitions, the research reveals that mindfulness practices enhance emotional regulation, foster adaptability, and improve team dynamics during periods of change. Participants reported that mindfulness created a